Effect of age and carcass weight on quality traits of m. rectus abdominis from Charolais heifers. (9th September 2016) - Ellies-Oury, M. P.; Dumont, R.; Perrier, G.; Roux, M.; Micol, D.; Picard, B.
Abstract : In practice cattle may be slaughtered at different combinations of age and weight. As each of these factors could affect meat quality traits, the present work aimed to identify which combination can be expected to increase overall meat quality of m. rectus abdominis of Charolais heifers. Totally, 40 heifers were slaughtered either at 26±1 or at 36±1 months of age. Young heifers were sampled at two different carcass weights (349±12 and 394±8 kg). Old heifers were also sampled at two different carcass weights (397±6 and 451±9 kg). The m. rectus abdominis was excised 24 h postmortem to determine metabolic enzyme activities, myosin heavy-chain isoform proportions, lipid contents, collagen content and collagen solubility. Shear force measurements were evaluated on raw and broiled meat after 14 days of ageing. Meat quality traits scored between 0 and 10 by sensory analysis. Increasing slaughter age from 26 to 36 months had no impact on either raw/broiled shear force (0.31⩽ P ⩽0.47) and/or meat quality traits (0.62⩽ P ⩽0.91) or on physicochemical properties of heifer's meat samples. Increasing carcass weight for a similar slaughter age of 26 months had also impact neither on meat quality traits (0.52⩽ P ⩽0.91) nor on muscular properties. On the contrary, increasing carcass weight for a similar slaughter age of 36 months had induced a decrease of muscular shear force (raw muscle; P= 0.009) and a concomitant decrease of total collagen content ( P =0.03). Nevertheless, no significant impact on meat quality traits was revealed by the sensorial panel (0.13⩽ P ⩽0.49). Metabolic enzyme activities (0.13⩽ P ⩽0.86) and myosin heavy-chain proportions (0.13⩽ P ⩽0.96) were not significantly impacted by slaughter age and carcass weight. Thus, the impact of increasing carcass weight and/or slaughter age in young Charolais heifers has a limited impact on meat quality traits and associated muscular characteristics. Modulating heifer's cycles (age and/or carcass weight in the studied range) appears to be a way to answer to the numerous marketing chains, without penalising meat quality traits.